The Promotion Effect of Low-Molecular Hydroxyl Compounds on the Nano-Photoelectrocatalytic Degradation of Fulvic Acid and Mechanism - Dong, Yifan; Li, Jinhua; Li, Xuejin; Zhou, Baoxue (Nano-Micro Letters, 2016)
A significant promotion effect of low-molecular hydroxyl compounds (LMHCs) was found in the nano-photoelectrocatalytic (NPEC) degradation of fulvic acid (FA), which is a typical kind of humic acid existing widely in natural water bodies, and its influence mechanism was proposed. A TiO2 nanotube arrays (TNAs) material is served as the photoanode. Methanol, ethanediol, and glycerol were chosen as the representative of LMHCs in this study. The adsorption performance of organics on the surface of TNAs was investigated by using the instantaneous photocurrent value. The adsorption constants of FA, methanol, ethanediol, and glycerol were 43.44, 19.32, 7.00, and 1.30, respectively, which indicates that FA has the strongest adsorption property. The degradation performance of these organics and their mixture were observed in a thin-layer reactor. It shows that FA could hardly achieve exhausted mineralization alone, while LMHCs could be easily oxidized completely in the same condition. The degradation degree of FA, which is added LMHCs, improves significantly and the best promotion effect is achieved by glycerol. The promotion effect of LMHCs in the degradation of FA could be contributed to the formation of a tremendous amount of hydroxyl radicals in the NPEC process. The hydroxyl radicals could facilitate the complete degradation of both FA and its intermediate products. Among the chosen LMHCs, glycerol molecule which has three hydroxyls could generate the most hydroxyl radicals and contribute the best effective promotion. This work provides a new way to promote the NPEC degradation of FA and a direction to remove humus from polluted water.